Systematic Review : Efek Resveratrol Terhadap Parameter Hipertensi - Raisya Zahra Salmalia; Rachmat Faisal Syamsu; Dwi Pratiwi Ma’ruf (Universitas Malahayati, 2026)
ABSTRACT Hypertension is a major global health issue with rising prevalence and significant morbidity and mortality. Despite available pharmacological therapies, blood pressure control often remains suboptimal, prompting investigation into natural adjunctive interventions. Resveratrol, a polyphenolic compound found predominantly in red grape skin, has demonstrated antioxidant, anti-inflammatory, and endothelial function-enhancing properties, suggesting potential antihypertensive effects. This systematic review aims to evaluate the impact of resveratrol on hypertension-related parameters in experimental animal models. A comprehensive literature search was conducted across PubMed, Scopus, Sinta, and Google Scholar for studies published between 2020 and 2025, focusing on in vivo interventions using pure resveratrol. Ten studies met inclusion criteria, encompassing models such as spontaneously hypertensive rats, DOCA-salt-induced hypertension, cyclosporin A-induced hypertension, and perinatal programming of hypertension. Consistently, resveratrol administration resulted in reduced systolic and diastolic blood pressure, enhanced endothelial nitric oxide (NO) bioavailability, decreased oxidative stress and inflammatory markers, and improved target organ function, particularly in the heart and kidneys. Mechanistically, effects were mediated via eNOS/NO pathway activation, modulation of renin-angiotensin-aldosterone system, antioxidative protection, anti-inflammatory activity, and regulation of cellular stress pathways. These findings support resveratrol as a promising adjunctive agent for hypertension management, offering both blood pressure-lowering and organ-protective benefits. Moreover, its presence in grapes, noted in the Quran for health benefits, highlights the potential for dietary incorporation as part of holistic health approaches. Further clinical studies are warranted to translate these experimental findings into human populations. Keywords: Resveratrol, Hypertension, Blood Pressure, Endothelial Function. ABSTRAK Hipertensi merupakan masalah kesehatan global dengan prevalensi yang terus meningkat dan kontribusi signifikan terhadap morbiditas serta mortalitas. Meskipun tersedia terapi farmakologis, pengendalian tekanan darah sering kali belum optimal, sehingga penelitian mengenai intervensi tambahan berbasis bahan alami menjadi penting. Resveratrol, senyawa polifenol yang terutama terdapat pada kulit anggur merah, memiliki sifat antioksidan, antiinflamasi, dan meningkatkan fungsi endotel, sehingga berpotensi menurunkan tekanan darah. Sistematic review ini bertujuan mengevaluasi efek resveratrol terhadap parameter hipertensi pada model hewan eksperimental. Pencarian literatur dilakukan di PubMed, Scopus, Sinta, dan Google Scholar untuk studi tahun 2020–2025 dengan intervensi resveratrol murni. Tujuh studi memenuhi kriteria inklusi, meliputi model tikus hipertensi spontan, hipertensi DOCA-salt, hipertensi akibat siklosporin A, dan pemrograman hipertensi perinatal. Secara konsisten, pemberian resveratrol menurunkan tekanan darah sistolik dan diastolik, meningkatkan bioavailabilitas nitric oxide (NO) endotel, menurunkan stres oksidatif dan biomarker inflamasi, serta memperbaiki fungsi organ target, terutama jantung dan ginjal. Mekanisme efek melibatkan aktivasi jalur eNOS/NO, modulasi sistem renin-angiotensin-aldosteron, perlindungan antioksidan, aktivitas antiinflamasi, dan regulasi jalur stres seluler. Temuan ini menunjukkan bahwa resveratrol berpotensi menjadi agen tambahan dalam pengelolaan hipertensi dengan manfaat proteksi organ. Selain itu, kandungan resveratrol dalam anggur, yang disebut dalam Al-Qur’an sebagai buah bermanfaat bagi kesehatan, mendukung potensi penggunaannya dalam pendekatan diet sehat. Studi klinis lebih lanjut diperlukan untuk mentranslasi hasil ini ke populasi manusia. Kata Kunci: Resveratrol, Hipertensi, Tekanan Darah, Fungsi Endotel.